The Administrative System of Human Resources Management and The Law of Civil Service at the National University of the Center of Peru -2018-2019 - Morales, Carmen (2021)
Civil Service Act, No. 30057, and its Regulations, establishes an employment regime for administrative workers, from 2014; its purpose is that, public entities reach higher levels of efficiency and efficiency, and effectively provide quality services through a better Civil Service, its purpose is to have a better understanding of the civil service. In the first part we present the background of public employment in Peru, until Law No. 30057 Law on Civil Service. We examine the reasons why the Office of Human Resources has not implemented this legal device, which will improve the strategies and policies, of human resources at the University, and provide a quality service. A Sample Survey of 95 workers was conducted between appointees and contractors. In the end we present our conclusions and recommendations.